# Reasoning Inequalities Quiz for SBI PO Pre 2019 and IBPS PO Pre 2019 Exams | Inequalities Questions PDF for SBI PO 2019 and IBPS PO 2019 at Smartkeeda

Directions: In these questions, relationship between different elements is shown in the statement. The statements are followed by two or three conclusions. Choose the correct Answer given below:
Important for :
1
Statements: R > I = N > P      Y ≥ R > K      N ≤ E < Z

Conclusions: K > I,         I < Z
» Explain it
A
Statements: R > I = N > P      Y ≥ R > K      N ≤ E < Z

Conclusions: K > I,         I < Z

For conclusion I: K > I

From the statements I and II, we get:

I < R > K

Here, the signs on inequalities between I and R are getting reversed. Conclusion I hence doesn't follow.

For conclusion II: I < Z

Combining statements I and III, we get:

I = N ≤ E < Z

Here, the common sign between I and Z is ‘<’ and the given conclusion is also I < Z. Hence, conclusion II follows.

Hence, the correct answer is would be ‘Only conclusion II follows’.
2
Statements:   T > K > Y ,    J ≤ K = G ,    I > C ≥ G ,  M ≤ I < N

Conclusions:  N > K ,    C ≤ T,     M < J
» Explain it
C
Statements:   T > K > Y ,    J ≤ K = G ,    I > C ≥ G ,  M ≤ I < N

Conclusions:  N > K ,    C ≤ T,     M < J

For Conclusion I: N > K

From statements II, III and IV, we get:

N > I > C ≥ G = K

Here, the common sign between N and K is '>'. Thus N > K.

Hence conclusion I follows.

For Conclusion II: C ≤ T

From statements I, II and III, we get:

C ≥ G = K < T

Here, we can see the opposite sign between C and  T , thus no relationship can be established between them.

Hence conclusion II does not follow.

For Conclusion III: M < J

From statements II, III and IV, we get:

M ≤ I > C ≥ G = K ≥ J

Here, we can see the opposite sign between M and J, thus no relationship can be established between them.

Hence conclusion III does not follow.

Therefore only conclusion I follows.

Hence option C is correct.
3
Statements:   B ≥ P = M ,    X > B < T,    Y = H ≤ X ,   R > Y > N

Conclusions:  P > H ,    P = H,     R > X
» Explain it
E
Statements:   B ≥ P = M ,    X > B < T,    Y = H ≤ X ,   R > Y > N

Conclusions:  P > H ,    P = H,     R > X

For Conclusion I: P > H

From statements I, II and III, we get:

H ≤ X > B ≥ P

Here, we can see the opposite sign between P and  H , thus no relationship can be established between them.

Hence conclusion I does not follow.

For Conclusion II: P = H

From statements I, II and III, we get:

H ≤ X > B ≥ P

Here, we can see the opposite sign between P and  H , thus no relationship can be established between them.

Hence conclusion II does not follow.

For Conclusion III: R > X

From statements II and III, we get:

R > Y = H ≤ X

Here, we can see the opposite sign between R and X, thus no relationship can be established between them.

Hence conclusion III does not follow.

Therefore none of the conclusions follows.

Hence option E is correct.
4
Statements:   F < G < D ,      D < H > C ,      F = C < A

Conclusions:  G < C ,      H = A
» Explain it
E
Statements:   F < G < D ,      D < H > C ,      F = C < A

Conclusions:  G < C ,      H = A

For conclusion I: G < C

From statements I and III, we get:

C = F < G

Here, the common sign between C and G is ‘<’. Hence C < G. Thus conclusion I does not follow.

For conclusion I: H = A

From statements II and III, we get:

H > C < A

Here, we get opposite signs between H and A. Thus no relationship can be established between them.

Hence conclusion II does not follow.

Therefore neither conclusion I nor II follows.

Hence option E is correct.
5
Statements:   C < H = J ,      X ≤ Y < J ,      N > X ≥ Z

Conclusions:  Y > Z ,      Y = Z
» Explain it
B
Statements:   C < H = J ,      X ≤ Y < J ,      N > X ≥ Z

Conclusions:  Y > Z ,      Y = Z

For conclusion I: Y > Z

From statements I and III, we get:

Y ≥ X ≥ Z

Here, the common sign between Y and Z is ‘≥’. Hence Y ≥ Z Thus conclusion I does not follow individually.

For conclusion II: Y = Z

From statements I and III, we get:

Y ≥ X ≥ Z

Here, the common sign between Y and Z is ‘≥’. Hence Y ≥ Z. Thus conclusion II also does not follow individually.

On combining conclusions I and II, we get: Y ≥ Z, which is the true relationship.

Thus either conclusion I or II follows.

Hence option B is correct.